Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(A=x-x^2=-\left(x^2-2.x.\frac{1}{2}+\frac{1}{4}\right)+\frac{1}{4}=-\left(x-\frac{1}{2}\right)^2+\frac{1}{4}\le\frac{1}{4}\)
Vậy Max A = \(\frac{1}{4}\Leftrightarrow x=\frac{1}{2}\)
b) \(B=2x-2x^2=2\left(x-x^2\right)=-2\left(x-\frac{1}{2}\right)^2+\frac{1}{2}\le\frac{1}{2}\)
Vậy Max B = \(\frac{1}{2}\Leftrightarrow x=\frac{1}{2}\)
a)(2x2+1)(3x3-2x2+3
= 6x5-4x4+6x2+3x3-2x2+3
= 6x5-4x4+3x3+4x2+3
b)(-3x+1)(4x4-x³+x)
= -12x5+3x4-3x2+4x4-x³+x
= -12x5+7x4-x3-3x2+x
a) \(\left(x^2+2xy+y^2\right):\left(x+y\right)\)
\(=\left(x+y\right)^2:\left(x+y\right)\)
\(=x+y\)
b) \(\left(125x^3+1\right):\left(5x+1\right)\)
\(=\left(5x+1\right)\left(25x^2-5x+1\right):\left(5x+1\right)\)
\(=25x^2-5x+1\)
c) \(\left(x^2-2xy+y^2\right):\left(y-x\right)\)
\(=\left(x-y\right)^2:\left(y-x\right)\)
\(=\left(y-x\right)^2:\left(y-x\right)\)
\(=y-x\)
a ) \(A=x-x^2=-\left(x^2-2.x.\frac{1}{2}+\frac{1}{4}\right)+\frac{1}{4}=-\left(x-\frac{1}{2}\right)^2+\frac{1}{4}\le\frac{1}{4}\)
Vậy MAX \(A=\frac{1}{4}\Leftrightarrow x=\frac{1}{2}\)
b) \(B=2x-2x^2=2\left(x-x^2\right)=-2\left(x-\frac{1}{2}\right)^2+\frac{1}{2}\le\frac{1}{2}\)
Vậy MAX \(B=\frac{1}{2}\Leftrightarrow x=\frac{1}{2}\)
\(\frac{x^7+x^2+1}{x^2+x+1}=\frac{x^2\cdot\left(1+x^5\right)+1}{x\cdot\left(x+1\right)+1}=\frac{x+x^6+1}{x+1+1}=\frac{x+1+1-1+x^6}{x+1+1}=1-\frac{1+x^6}{x+1+1}\)